The influence of the American new right on public policy making (a study of the speeches of republican party candidates) for the 2024 US elections. - Assistant lectures :Faten Ali Awead (The college of law and political science journal, 2025)
The traditional American right, which is represented by the Republican Party. These groups generally agree in their rejection of immigration, whether regular or irregular, and do not recognize any rights for homosexuality, nor the right for women to have an abortion, denounce freedom of trade, reject secularism, and even oppose democracy that allowed Biden and the Democrats to triumph over Trump and the Republican Party. On the external side, the New Right worked to combat illegal immigration and was hostile to Muslims, holding it responsible for harming societal security and peace and destroying the economy by exploiting opportunities at the expense of the American citizen, in addition to that great interest in Russia and concern about the growing power of China and the emphasis on the Iranian nuclear program and clear support, material and moral, for the Zionist entity.